Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Materi Rotasi dan Revolusi Bumi di Kelas VI - Rezza Amanda pratiwi; Arie Widya Murni; Rosyidah Umami Octavia (Pengenalan Lapangan Persekolahan Pendidikan Guru Sekolah Dasar, 2026)
This Classroom Action Research (CAR) aims to improve students' learning achievement in the field of Natural and Social Sciences (IPAS) related to the topic of Earth's rotation and revolution by implementing the Problem Based Learning (PBL) model supported by the Paroreb media (Earth Rotation and Revolution Board). The subjects involved in this study were 25 students from grade VI of SDN Pucang 4. The research was conducted in two cycles, which included the stages of planning, action implementation, observation, and reflection. From the observations in the pre-cycle, it was found that the learning mastery level only reached 45%, indicating students' low understanding of the concepts of Earth's rotation and revolution. In cycle I, after implementing the PBL model with the support of Par media, the learning mastery level increased to 60%. Improvements made in cycle II resulted in a better mastery level, namely 88%. This increase indicates that the use of the PBL model together with the media